2016
DOI: 10.4314/thrb.v18i3.3
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, practice and factors associated with poor compliance with universal precautions among healthcare workers at Bugando Medical Centre, Mwanza, Tanzania

Abstract: Background: Healthcare workers (HCWs) are exposed to blood-borne infections by pathogens, such as HIV, and Hepatitis B and C viruses, as they perform their clinical activities in hospitals. Compliance with universal precautions has been shown to reduce the risk of exposure to these pathogens. This aimed at assessing the knowledge, practices and factors associated with poor compliance to universal precautions among HCWs at Bugando Medical Centre in Mwanza, Tanzania.Methods: This was a cross sectional study carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
2
1
Order By: Relevance
“…23 The present finding was similar to the prevalence of anemia among women with cervical cancer (50.95%) in Tikur Anbesa, Ethiopia. 22 On the other hand, the prevalence of anemia among patients with malignant cancer in our study was much lower than that reported among patients with cancer in Tanzania (77%), 20 and women with cervical cancer in Nigeria (68.1%). 19 Notwithstanding, the 50.3% prevalence in the current study was much higher than that reported in Addis Ababa, Ethiopia (23%), 18 the Kingdom of Saudi Arabia (44.1%), 16 and Sana'a, Yemen (21.7%).…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…23 The present finding was similar to the prevalence of anemia among women with cervical cancer (50.95%) in Tikur Anbesa, Ethiopia. 22 On the other hand, the prevalence of anemia among patients with malignant cancer in our study was much lower than that reported among patients with cancer in Tanzania (77%), 20 and women with cervical cancer in Nigeria (68.1%). 19 Notwithstanding, the 50.3% prevalence in the current study was much higher than that reported in Addis Ababa, Ethiopia (23%), 18 the Kingdom of Saudi Arabia (44.1%), 16 and Sana'a, Yemen (21.7%).…”
Section: Discussioncontrasting
confidence: 77%
“…8,18 While several studies have been conducted on anemia among patients with cancer in Africa, 19 published data on anemia in patients with cancer in Sudan is scarce. 11,20 Investigations of anemia among patients with cancer is of paramount importance as they could yield the data necessary for interventions. Caregivers and health planners need data on anemia among patients with cancer so that it can be used in evidence-based practice.…”
Section: Introductionmentioning
confidence: 99%
“… 20 , 21 This result is higher than in the studies into respondent compliance with SPs conducted at Gondar University Comprehensive Specialized Hospital (12%), 6 in West Arsi Zone (36.3%), 14 and in Northern Cyprus (30.6%). 22 When our results are compared with studies conducted in Dawuro Zone 18 and Tanzania, 23 in which 65.0% and 77% of HCWs complied with standard precautions, respectively, we found a low level of compliance.…”
Section: Discussionmentioning
confidence: 44%